Inventing modern adolescence : the children of immigrants in turn-of-the-century America - Chinn, Sarah E. (Rutgers series in childhood studies., 2009)
The 1960s are commonly considered to be the beginning of a distinct "teenage culture" in America. But did this highly visible era of free love and rock 'n' roll really mark the start of adolescent defiance? In Inventing Modern Adolescence Sarah E. Chinn follows the roots of American teenage identity further back, to the end of the nineteenth and beginning of the twentieth centuries. She argues that the concept of the "generation gap"--A stereotypical complaint against American teens-actually originated with the division between immigrant parents and their American-born or -r